1998
DOI: 10.1063/1.121656
|View full text |Cite
|
Sign up to set email alerts
|

Erbium doping of LiNbO3 by the ion exchange process

Abstract: Erbium-doped LiNbO3 slides are fabricated by the ion exchange process. Compositional in-depth profiles of the species involved in the exchange are obtained by secondary ion mass spectrometry. Spectroscopic properties of Er3+ ions in the matrix are determined by photoluminescence spectroscopy. Structural and spectroscopic analyses suggest the formation of two different microstructures in the exchanged region. The potential of ion exchange for a controlled doping of LiNbO3 is outlined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…The first region (I) corresponds to the very surface layer where the iron concentration is highest (about 5 × 10 26 to 3 × 10 28 at/m 3 ); the second one (II) plays the role of a transient region and, finally, the third region (III) is close to the substrate and displays a semi-Gaussian iron decay. This behaviour is similar to that observed in the erbium doping by the ion exchange process [10] where the surface region plays the role of a reservoir for the further in-diffusion of the dopant into the matrix. It is worth mentioning that in the regions I and II, a lithium accumulation is evident and the iron strain profile does not correspond to the compositional one suggesting a deviation from the Vegard law.…”
Section: Discussionsupporting
confidence: 77%
“…The first region (I) corresponds to the very surface layer where the iron concentration is highest (about 5 × 10 26 to 3 × 10 28 at/m 3 ); the second one (II) plays the role of a transient region and, finally, the third region (III) is close to the substrate and displays a semi-Gaussian iron decay. This behaviour is similar to that observed in the erbium doping by the ion exchange process [10] where the surface region plays the role of a reservoir for the further in-diffusion of the dopant into the matrix. It is worth mentioning that in the regions I and II, a lithium accumulation is evident and the iron strain profile does not correspond to the compositional one suggesting a deviation from the Vegard law.…”
Section: Discussionsupporting
confidence: 77%
“…Preliminary results of our experiments with a low (or moderate-temperature) diffusion of erbium ions into lithium niobate have been already reported 1921 and some of them have been later confirmed also by Sada et al 22• During our study of moderate temperature diffusion processes we have understood the importance of different crystallographic structure of the lithium niobate substrate wafers, which are commonly used as material for optoelectronics. Different hardness of the Z and X lithium niobate cuts, as well as not the same way of incorporation of W during the proton exchange fabrication procedures, moreover different properties of the resulting APE waveguides fabricated in the both cuts under the same experimental conditions, made us to search for a general explanation of the common features of the matter.…”
Section: Introductionsupporting
confidence: 61%
“…Therefor we explained'9'20 the different behavior of the particular types of the cuts on the bases of different rates of the diffusion processes. Sada et al 22 suggested, that an important role is played by the different surface density of lithium ions in the X-cuts and Z-cuts, as well as the different mobility in film-diffusion of ions. The erbium diffusion into…”
Section: Moderate-temperature Er Doping Into Lithium Niobatementioning
confidence: 99%
“…Temperature and duration of ion exchange treatment were varied in the ranges from 613 to 656 o C, and from 78 to 111.5 hrs, respectively. In contrast to previously developed process parameters [7], we used a low ramp rate (100 °C/h) during both heating and cooling down of the salt mixture. Such modification of fabrication technique was used to avoid surface damage, which otherwise degrades the optical properties of the crystals [8].…”
Section: Fabrication Techniques and Characterization Methodsmentioning
confidence: 99%
“…Thus, the upconversion can be suppressed by a proper choice of doping technology [2,3] and/or postdoping processing [4,6], which may provide as sufficient decreasing the relative concentration of clustered ions [3,4,6] as well as a strong alteration of electron-phonon coupling via variation either a lattice site of Er 3+ ion [4,5] or a phonon spectrum of host [2,5]. In light of the wellestablished limitations [2,6] of Er indiffusion technique, Er exchange technique, inducing unusual chemical bonding rearrangement and evident crystal structure modification [7], appears to open the new possibilities for selective manipulation of phonon-assisted processes in Er:LiNbO 3 and, hence, for suppression of upconversion.…”
Section: Introductionmentioning
confidence: 99%